MODALITAS DALAM FILM KOMEDI KEMBANG POLARIA II SUATU KAJIAN LINGUISTIK FUNGSIONAL SISTEMIK - Mariyadi Mariyadi; Sesilya Saman Madeten; Sesilia Seli (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study is to reveal the use of modalities in a comedy movieentitled Kembang Polaria (FKKP) II. Specifically this study investigate thetypes, values, and frequency of use of modalities in that movie. This studyutilizes qualitative and quantitative descriptive methods with the SystemicFunctional Linguistics (LFS) approach in assessing the modalities clauses inFKKP II obtained through library techniques. The findings indicate that theuse of probability modality is high, medium, and low, usuality modality obtainshigh value, medium and low value for obligation modality, and medium andlow value in inclination modality. The possibility modality is used for 12 timesand the modality of the frequency is used 6 times. Obligation modality is used25 times and inclination modulation was found to be used 43 times. Thedominant modality in the movie (FKKP II) is modulation modality, which is79.07% of the total modality used. The modalities found in FKKP II aremodality modulation with medium and high values, obligation modality hashigh value, and high value for inclination modulation. In conclusion, thehighest authority is not used in the movie (FKKP II) since most of the movieplayers are the general public members who have the same position in sociallife.Keywords: modallity, LFS, Kembang Polaria II, Interpersonal